2016
DOI: 10.1111/ppa.12581
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of pyramiding of three quantitative resistance loci to apple scab

Abstract: Quantitative plant resistance is supposed to be more durable than qualitative resistance for the control of plant diseases. However, it has been experimentally shown that erosion of quantitative resistance can occur. Cumulation of quantitative resistance loci (QRLs) in the same cultivar is considered to improve the efficiency and durability of quantitative resistance, but the choice of QRLs to be combined is of crucial importance. This study investigated whether the combination of QRLs acting on different stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 39 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…We also envisage varying the mutation probabilities (τ g and τ w ), cost of infectivity (θ g ), cost of aggressiveness (θ w ), and number of steps to erode a trait for quantitative resistance (Q w ), to simulate various possible choices of major genes and traits for quantitative resistance. It would also be of interest to simulate and investigate the potential for combinations of several sources of quantitative resistance, whose performance on disease severity has been experimentally demonstrated [ 144 ]. Finally, we will also explore different spatiotemporal strategies to deploy plant resistance to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…We also envisage varying the mutation probabilities (τ g and τ w ), cost of infectivity (θ g ), cost of aggressiveness (θ w ), and number of steps to erode a trait for quantitative resistance (Q w ), to simulate various possible choices of major genes and traits for quantitative resistance. It would also be of interest to simulate and investigate the potential for combinations of several sources of quantitative resistance, whose performance on disease severity has been experimentally demonstrated [ 144 ]. Finally, we will also explore different spatiotemporal strategies to deploy plant resistance to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…QTL acting at different stages of plant development, corresponding to different stages of the pathogen infection cycle, were also identified in two wheat cultivars with durable resistance to yellow rust ( Dedryver et al, 2009 ). In apple, the pyramiding of three resistance QTL to scab was suggested to result in more durable resistance since the QTL were shown to act at different stages of the fungal infection cycle, from as soon as it penetrated the plant to a later stage during subcutaneous growth and sporulation ( Laloi et al, 2016 ). In pea NILs, combinations of resistance QTL individually acting on delaying symptom appearance and/or on slowing down root colonization by Aphanomyces euteiches had an increased action on the two pathogen life-history traits ( Lavaud et al, 2016 ).…”
Section: Quantitative Disease Resistance: Integration Into Pyramidingmentioning
confidence: 99%
“…Moreover, diversifying resistance mechanisms is expected to promote conflicting selection pressures on the pathogen populations, which should constrain them to an evolutionary compromise limiting their development. Indeed, Laloi et al [95] showed that the combination of QTLs acting on different stages of pathogen development, and thus probably based on different mechanisms, could improve the efficiency of resistance in the apple scab pathosystem.…”
Section: Discussionmentioning
confidence: 99%